DEVELOPMENT OF DIAGNOSTIC METHOD’S REALIZING ALGORITHM OF THE EQUIPPED WITH THE COURSE STABILITY SYSTEM VEHICLES AT OPERATION STAGE - Il. V. Denisov; I. A. Terentyev (Вестник СибАДИ)
Introduction. Thanks to the development of microelectronics the design of modern vehicles is saturated with microprocessor control systems. Equipping of transport machines by the course stability system, adopted at the legislative level abroad and planned in the Russian Federation in the nearest years, requires the adaptation of domestic normative-technical documentation for possibility of diagnostics, maintenance and current repair of automobiles. Such situation appeared due to the lack of effective method of diagnostics vehicles with mechatronic control systems during operation. Consequently, it is not possible at the automobile service enterprises to assess the changing in the technical condition of the transport machines at once, as well as to monitor the adequacy control of the governing decisions.Materials and methods. The research proves the increase in efficiency of the vehicles’ diagnostic procedure with course stability system due to the implementation of three-stage system, proposed by the authors of the article and compared to two-stage, which is currently being implemented at automobile service enterprises.Results. As a result, realizing algorithm of the transport machines’ diagnostic method, equipped with the course stability system and based on the three-stage system of technical diagnostics was developed and implemented.Discussion and conclusions. Application of realizing algorithm at automobile service enterprises would assess the automobiles’ technical condition with mechatronic control systems at operation stage and would help to monitor the governing decisions’ adequacy, to predict residual resource and give recommendations on necessary mode and volume of maintenance and current repair.